Fast Growing of Pancreas Cancer in a Patient with Familial Susceptibility - Del Chiaro, Marco; Rangelova, Elena; Ansorge, Christoph; Blomberg, John; Andren-Sandberg, Åke; Segersvärd, Ralf (JOP. Journal of the Pancreas, 2012)
Context A positive family history is a well defined risk factor for the development of pancreatic cancer. However, data is scarce regarding time of progression in these families and no clear guidelines are available about time interval and modality when to follow these individuals. Case report A 47-year-old male with two first-degree relatives dead of pancreatic cancer (mother 53 and sister 40 years, respectively). In 2007 at the age of 43, the patient was included into a screening program by annual CT scans at a community hospital. In 2009, after two years of negative screening, it was suggested to increase the interval to biannual CTs. At the beginning of 2011 the patient was admitted due to abdominal pain and jaundice. Imaging showed a 3 cm large tumor in the head of the pancreas with encasement of a replaced right hepatic artery from the superior mesenteric artery. The patient underwent total pancreatectomy with en block resection of the right hepatic artery, rebuilt by a rotation end-to-end anastomosis to the splenic artery. Histology showed pancreatic ductal adenocarcinoma (pT3, pN1, pM0). At 12-month follow up no recurrence has been detected. Conclusion A positive familial history is a risk factor to develop pancreatic cancer. In this family, as suggested by the EUROPAC, two first-degree affected, with a cumulative age at the diagnosis less than 110 years, is an important risk factor. The current case suggests that an annual screening seems reasonable and safer than longer intervals of time.